2005
DOI: 10.1359/jbmr.041126
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human TSH Modulates In Vivo C-Telopeptides of Type-1 Collagen and Bone Alkaline Phosphatase, but Not Osteoprotegerin Production in Postmenopausal Women Monitored for Differentiated Thyroid Carcinoma

Abstract: In women monitored for thyroid carcinoma, short-term stimulation with rhTSH induced an acute decrease in serum C-telopeptides of type-1 collagen and an increase in serum BALP levels without any effect on OPG production. The inhibitory effect of TSH on bone resorption occurred only in postmenopausal women who showed low BMD and a high bone turnover rate as an effect of L-thyroxine suppressive therapy.Introduction: It has been recently shown that thyrotropin (TSH) has an inhibitory activity on skeletal remodelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 39 publications
(106 reference statements)
3
84
2
1
Order By: Relevance
“…In contrast, the over-expression of constitutively activated TSHR in osteoclast precursor cells [64] or transgenically, in mouse precursors [73] inhibited osteoclastogenesis. In post-menopausal women, a single subcutaneous injection of TSH drastically lowered serum C-telopeptide to premenopausal levels within 2 days, with recovery at day 7 [71]. In none of the studies with TSH replacement did thyroid hormones increase, exemplifying again that the pituitary-bone axis is more primitive than the pituitary-thyroid axis.…”
Section: Mechanism Of Actionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, the over-expression of constitutively activated TSHR in osteoclast precursor cells [64] or transgenically, in mouse precursors [73] inhibited osteoclastogenesis. In post-menopausal women, a single subcutaneous injection of TSH drastically lowered serum C-telopeptide to premenopausal levels within 2 days, with recovery at day 7 [71]. In none of the studies with TSH replacement did thyroid hormones increase, exemplifying again that the pituitary-bone axis is more primitive than the pituitary-thyroid axis.…”
Section: Mechanism Of Actionmentioning
confidence: 96%
“…At least 20 clinical studies have since documented tight and highly reproducible correlations between low TSH levels, bone loss, bone geometry, and fracture risk in patient cohorts across the globe . Evidence also shows that TSH protects the skeleton by exerting anti-resorptive and anabolic actions in rodent models and in people [37,[62][63][64][65][66][67][68][69][70][71].…”
Section: Thyroid Stimulating Hormonementioning
confidence: 99%
“…On this basis, rhTSH administration is clinically safe and may have beneficial effects on the vascular system by reducing arterial blood pressure and increasing circulating nitric oxide (55). Moreover, in postmenopausal, but not in premenopausal women, monitored for DTC, rhTSH administration acutely decreases the serum C-telopeptides of type-1 collagen and increases serum bone alkaline phosphatase levels, but does not affect osteoprotegerin production (56). Thus, an acute increase in serum TSH concentration leads to a marked inhibition of bone resorption.…”
Section: The Alternative Use Of Rhtshmentioning
confidence: 99%
“…In the context of conflicting data on a functional role for TSH in skeletal development, our data, which were corrected for serum TSH levels, outline the importance of local T 3 for bone metabolism. (13)(14)(15)(16)(17)(35)(36)(37)(38) Two recent papers by Bassett and colleagues, (18,19) who studied mice with complete or haploinsufficiency of TRa and -b, concluded that TRa regulates both skeletal development and adult bone maintenance.…”
Section: Discussionmentioning
confidence: 99%